Struktur trofik komunitas ikan di Sungai Cisadea Kabupaten Cianjur, Jawa Barat [Trophic structure of fish community in Cisadea River, Cianjur, Jawa Barat] - Epa Paujiah; Dedy Duryadi Solihin; Ridwan Affandi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2013)
Interactions in fish community in an ecosystem can be assessed through food habits analysis. This study aims to assess the trophic structure of fish communities in Cisadea River. Fishes were collected using active and passive fishing gear at six locations representing upstream, midstream, and downstream areas at the dry season (June-November 2012). During the observation, sample was caught of 666 individuals consists of 48 species. A total of 250 individuals were analyzed for their food composition and digestive tract morphology to determine their trophic groups. Based on large group of organisms, fish community in Cisadea River consists three guild is carnivorous, omnivorous and herbivorous fish which dominated by carnivore and omnivore fish. Based on food organism taxon, the fishes were assigned to four groups i.e. insectivore, phy-toplanktivore, crustacivore, and molluscivore, with eight groups of food organisms (phytoplankton, insects, macrophytes, crustaceans, mollusc, fish, protozoa, and rotifers). In the upstream and midstream areas, the primary diet was insects and algae, whereas in the downstream the diet consists of algae, crustaceans, and insects. Abstrak Interaksi yang terjadi pada suatu komunitas ikan dapat dikaji melalui analisis makanan alaminya. Penelitian ini bertu-juan untuk mengkaji struktur trofik komunitas ikan di Sungai Cisadea. Ikan dikoleksi dengan menggunakan alat tang-kap aktif dan pasif di enam lokasi yang mewakili wilayah bagian hulu, tengah dan hilir selama musim kemarau (Juni-November 2012). Selama pengamatan, sampel yang diperoleh sebanyak 666 individu yang termasuk dalam 48 spesies. Sebanyak 250 individu dianalisis komposisi makanannya dan morfologi saluran pencernaannya untuk mengetahui ke-lompok trofik pada komunitas ikan tersebut. Berdasarkan golongan besar organismenya, komunitas ikan di Sungai Cisadea terdiri atas tiga kelompok, yaitu karnivora, omnivora, dan herbivora dengan kelompok ikan yang mendominasi adalah ikan omnivora dan karnivora. Berdasarkan takson organisme makanannya, komunitas ikan di Sungai Cisadea dibagi menjadi empat kelompok, yaitu insektivora, fitoplanktivora, krustasivora, dan moluskivora. Kelompok takson organisme makanannya ialah fitoplankton, insekta, makrofita, krustase, moluska, ikan, protozoa, dan rotifer. Di wilayah sungai bagian hulu dan tengah makanan utama ikan terdiri atas insekta dan alga, sedangkan di bagian hilir terdiri atas alga, krustase, dan insekta.